Arus kuat STUDI KELAYAKAN INSTALASI LISTRIK PADA GEDUNG STASIUN PENGISIAN BAHAN BAKAR UMUM (SPBU) PERNEK SUMBAWA - Agus Hermansyah Agus; Ahmad Jaya; Indra Darmawan; Desi Maulidyawati (Program Studi Teknik Elektro, 2025)
Human development cannot be separated from technology, especially electrical energy which functions as the main support in various daily activities. The use of electricity must be balanced with attention to maintenance and installation updates to avoid risks that could harm users. Several important aspects in electrical installations include the selection of materials, the installation process, and compliance with applicable regulatory standards. This research uses qualitative methods, which focus on in-depth analysis of the study object through observation, interviews, and testing of electrical installations in the laboratory. This is different from the method While the quantitative approach involves statistical analysis, the qualitative approach places more emphasis on collecting, analyzing and interpreting data to understand social problems based on natural reality. Hani from research shows that the electrical installation in the Pernek gas station building meets PUIL 2011 standards. This feasibility is determined by several factors such as panel height, contact box, switch, KWH meter, cable color, and the use of MCB as a safety cable in electrical installations are differentiated based on color: R phase is black, S phase is brown, T phase is gray, N cable is blue, and grounding cable is green-yellow. The research conclusions confirm that all installation elements-including cable color, height of contact boxes, switches, panels, KWH meters, and MCB-comply with PUII provisions. 2011 and applicable regulatory standards